Evaluation of Linezolid and Vancomycin in the treatment of Methicillin-Resistant Staphylococcus aureus(MRSA) in Cystic Fibrosis Patients - Caulder, Celeste R.; Bookstaver, P. Brandon; Brown, David E.; Brown, Daniel (International Journal of Pharmacology and Toxicology, 2013)
Background:  Cystic fibrosis (CF) patients often have pulmonary colonization with multiple organisms, including MRSA, resulting in frequent hospitalizations and decreased quality of life.  The pupose of this study was to evaluate the clinical efficacy of linezolid (LZD) and vancomycin (VAN) in the treatment of MRSA in the CF population. Methods:  A case series study was conducted with CF patients with pulmonary exacerbation and sputum culture positive for MRSA. Patients were received intravenous LZD or VAN.  The primary endpoint was microbiological eradication of MRSA and secondary endpoints included Kanga Clinical Score (KS) and change in quality of life questionaire (CF QOL) score. Patients were followed for 6 months post treatment.  Results:  Eight subjects were randomized to receive LZD (n=5) or VAN (n=3), with average duration of therapy of 19.8 and 21 days, respectively.  The primary endpoint of microbiological eradication at end of treatment (EOT) was achieved in 3 patients treated with LZD and 2 with VAN.   KS calculated at baseline and EOT showed a significant decrease in all subjects from a median of 26/50 to 16/50.  Six patients or caregivers completed the CF QOL questionnaire.  Five patients (2 treated with LZD, 3 with VAN) had improvements in CFQOL scores at EOT.  No clinically significant adverse events were noted during the study. Conclusions:  No difference was noted between VAN and LZD in eradication of MRSA in CF patients with pulmonary exacerbation, nor in improvement in KS or CF QOL. Eradication of MRSA was less likely in patients with long-standing infection.